Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1073/pnas.2202563119
|View full text |Cite
|
Sign up to set email alerts
|

Self-driven carbon atom implantation into fullerene embedding metal–carbon cluster

Abstract: Hundreds of members have been synthesized and versatile applications have been promised for endofullerenes (EFs) in the past 30 y. However, the formation mechanism of EFs is still a long-standing puzzle to chemists, especially the mechanism of embedding clusters into charged carbon cages. Here, based on synthesis and structures of two representative vanadium–scandium–carbido/carbide EFs, VSc 2 C@ I h (7)-C 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…10 The first category includes mono-, di-, and trimetallofullerenes, 104–109 as well as cluster metallofullerenes 110 ( e.g. oxide clusters, 103 nitride clusters, 111–113 cyano clusters, 114 sulfide clusters, and carbide clusters), 10,97–99,115–120 while the second category includes H 2 , noble gases, 121 water and other non-metal guests. 10,100 (Fig.…”
Section: Fullerene Host–guest Chemistrymentioning
confidence: 99%
“…10 The first category includes mono-, di-, and trimetallofullerenes, 104–109 as well as cluster metallofullerenes 110 ( e.g. oxide clusters, 103 nitride clusters, 111–113 cyano clusters, 114 sulfide clusters, and carbide clusters), 10,97–99,115–120 while the second category includes H 2 , noble gases, 121 water and other non-metal guests. 10,100 (Fig.…”
Section: Fullerene Host–guest Chemistrymentioning
confidence: 99%
“…25 In 2014, Duck et al proposed that charge transfer is a principal factor that guides the bottom-up formation of endohedral mono-metallofullerenes. 26 Recently, Guan et al 27 and Yao et al 28 found that as-formed metallofullerenes can capture atomic carbon and its dimer.…”
Section: Introductionmentioning
confidence: 99%
“…Different from NCFs, metal carbido clusterfullerenes offer an opportunity to stabilize metal-nonmetal double bonds, which however require involvement of nonrare earth metals, including transition metals (titanium (Ti), vanadium­(V)) or actinide metal U with higher valence states than +3 of most trivalent rare-earth metals. Several metal carbido clusterfullerenes containing TiC double bonds have been identified in TiM 2 C@C 80 (M = Lu, Tb, Dy, Sc) by single-crystal X-ray diffraction, together with two M–C single bonds. , Instead, upon encapsulating Ti into the fullerene cage in the form of NCFs, Ti–N single bonds along with two M–N single bonds exist within TiM 2 N@C 80 (M = Sc, Y, see Scheme ). , This discrepancy results from the fact that fewer valence bonds (three) are normally required for N than those (four) for C. These reports stimulate us to involve Ti together with a lanthanide metal cerium (Ce) to construct a transition metal-lanthanide heteronuclear nitride clusterfullerene TiCeN@C 84 .…”
Section: Results and Discussionmentioning
confidence: 99%